Relative Linguistic Clues to Fancy Expressions - Al-Thunaibat , Sate’; Bani Atta , Ahmed Ibrahim (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aims at a relative description that can be relied upon for the purpose of a consistent and appropriate placement of these terms in their context on the approach of the Arabs in their speech and poetry, and to put them down to the places in which they were originally placed, and to indicate their discriminatory features, which helps to use them accurately in expression. Methods: The research took a descriptive and analytical approach based on tracking the positions of these words in some poetic models in the era of protest, and analyzing them in the light of verbal and moral clues. I came to her. Results: The study revealed the linguistic criteria that predict the emergence of contextual semantic components, and showed that similar utterances in predicates increase their chances of succession in the same context, and the contextual significance is gained through the regularity of utterances in contexts controlled by verbal and semantic clues, and that they dominate the context. Conclusion: The study concluded that a relative linguistic standard for the expressions of passion in the light of the verbal and intangible clues, emphasizing the attention of the Arabs to the meanings and expressions indicated by them through their grammatical positions describing some of their contextual cases, revealing the semantic features they carry, and clarifying the relationships of convergence or divergence between them, which helps to Employing it accurately in the appropriate context, and coming up with a relative linguistic standard for each word, especially since each word has a life story in its consistency with these standards, which had a role in producing the semantic difference displacing it from the rest of its sisters of the words of passion.